Seismogenic sources and related active faults in the gulf of Corinth; a combined approach - Segou, M.; Lozios, S. (Bulletin of the Geological Society of Greece, 2007)
The neotectonic graben of Corinth gulf forms an interesting case study from the geodynamical and seismological point of view, since specific characteristics met on the fault zones around the gulf and the adjacent seismological data pose several questions related with the overall modern activity across a number of neotectonic faults. Indexing active fault zones with structural, seismological and sedimentological criteria leads to thorough understanding of the evolution and modern activity and provide researchers useful tools in order to evaluate the degree of present day activity of the broader area. The combined approach proposed here, with joint use of both, seismogenic sources and structural evidence, contributes to the re-evaluation of the earthquake potential by assessing the role of active features in the already complex geodynamic environment of the Corinthian gulf